How Fathers Protect: Self-Concept as the Key Mechanism Linking Paternal Involvement to Reduced Risk Behaviors in School Adolescents - Arini, Diana Putri; Riyanto (Universitas Ahmad Dahlan, 2026)
Adolescent risk-taking behaviors in schools remain a pressing concern. Although father involvement and a positive self-concept are recognized protective factors, the psychological mechanism linking them requires clarification, particularly in the Indonesian context. This study examined whether self-concept mediates the relationship between father involvement and risk-taking behavior among Indonesian junior and senior high school students. A cross-sectional design was employed with 331 students from Palembang, South Sumatra. Data were collected using the Perceived Father Involvement Inventory (PFII), the Self-Concept Scale, and the Risk-Taking Behavior Scale. Mediation analysis with bootstrapping in Jamovi showed a significant total effect of father involvement on risk-taking behavior (β = −0.0388, p = .012). Importantly, the indirect effect via self-concept was significant (β = −0.0221, p = .004), whereas the direct effect was nonsignificant (β = −0.0167, p = .323), indicating a pattern consistent with indirect-only (full statistical) mediation. These findings suggest that the association between father involvement and lower risk-taking is primarily explained through its relationship with a more positive adolescent self-concept rather than through a direct effect. Accordingly, school-based prevention programs may benefit from a dual approach: engaging fathers as partners in adolescents’ identity development and implementing self-concept enhancement initiatives for students.